A Simple Spectrophotometric Method for Determination of Glyoxylic Acid in Its Synthesis Mixture - Mazhar Abdulwahed; Lamia Mamoly; Wael Bosnali (International Journal of Analytical Chemistry)
A new simple and reliable spectrophotometric method is described to determine glyoxylic acid in its synthesis reaction mixture containing oxalic acid, glycolic acid, acetic acid, glyoxal, and ethylene glycol by means of a modified Hopkins–Cole reaction between glyoxylic acid and tryptophan in presence of ferric chloride and concentrated sulphuric acid. The linear range of glyoxylic acid concentration is 0–0.028 M. The limits of detection (LOD) and quantitation (LOQ) are 0.0019 M and 0.00577 M, respectively. The LOD, LOQ, standard deviation, relative standard deviation, and recovery ratio of the proposed method are comparable with a selected HPLC reference method. Both methods displayed same precision and credibility. Reaction stoichiometry between tryptophan and glyoxylic acid is assumed to be 2 : 3. Reaction mechanism has been postulated based on identified molar ratios of reactants. Glyoxal gave a negative test with tryptophan although it is a dialdehyde.